2023
DOI: 10.1111/jen.13171
|View full text |Cite
|
Sign up to set email alerts
|

Insights into varroa mite (Varroa destructor) infestation levels in local honeybee (Apis mellifera) colonies of Ethiopia

Abstract: The varroa mite (Varroa destructor) is the most economically important parasitic pest of honey bees (Apis mellifera) that causes global colony decline and loss. Since its first detection in Ethiopia in 2010, little is known about the current infestation levels and contributing factors to the mite's distribution across the country. In this study, we conducted a large‐scale assessment of varroa prevalence and infestation levels in managed colonies across three potential beekeeping regions of Ethiopia; Oromia, Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Several studies conducted in Ethiopia have examined the prevalence of Varroa infestation in honeybee colonies and reported a high prevalence ranging from 30.5% to 91.8%. Furthermore, the infestation has been reported to have significant detrimental effects on both honeybee colonies and honey production, posing a considerable challenge for the country's beekeeping industry ( Begna, 2015 ; Godifey, 2015 ; Mezgabu et al, 2016 ; Nega et al, 2019 ; Shegaw et al, 2022 ; Gela et al, 2023 ). Furthermore, studies have shown that Ethiopian honey bee antennae exhibit an increased level of gene expression of the odorant binding protein OBP14, suggesting a potential improvement in detection and elimination of reproducing mites ( Gebremedhn et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies conducted in Ethiopia have examined the prevalence of Varroa infestation in honeybee colonies and reported a high prevalence ranging from 30.5% to 91.8%. Furthermore, the infestation has been reported to have significant detrimental effects on both honeybee colonies and honey production, posing a considerable challenge for the country's beekeeping industry ( Begna, 2015 ; Godifey, 2015 ; Mezgabu et al, 2016 ; Nega et al, 2019 ; Shegaw et al, 2022 ; Gela et al, 2023 ). Furthermore, studies have shown that Ethiopian honey bee antennae exhibit an increased level of gene expression of the odorant binding protein OBP14, suggesting a potential improvement in detection and elimination of reproducing mites ( Gebremedhn et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These disease assaults continue to have a serious effect on honeybees and their products, despite the lack of many solid kinds of research on the effects of the disease ( Shegaw et al, 2022 ). Varroosis is one of the serious honeybee diseases that affected honey production in Ethiopia ( Begna, 2006 ; Shegaw et al, 2022 ; Gela et al, 2023 ). However, evidence on the magnitude and distribution of varroa mites is still insufficient ( Godifey, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some honey bee populations have been identified as tolerant against this pest and able to survive even without anti-varroa treatment [ 12 , 13 , 14 , 15 ]. Since the detection of varroa for the first time in northern Ethiopia’s Tigray region [ 16 ], several studies have been conducted on its distribution and prevalence in the country [ 17 , 18 , 19 ]. A national survey conducted in Ethiopia, which covered all regions except Tigray, showed a wide distribution and up to 95.8% prevalence in the country with a significant variation between regions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the detection of varroa for the first time in northern Ethiopia’s Tigray region [ 16 ], several studies have been conducted on its distribution and prevalence in the country [ 17 , 18 , 19 ]. A national survey conducted in Ethiopia, which covered all regions except Tigray, showed a wide distribution and up to 95.8% prevalence in the country with a significant variation between regions [ 18 ]. The prevalence of varroa in Ethiopia was reported to be influenced by several factors including agroecology and management systems [ 19 ].…”
Section: Introductionmentioning
confidence: 99%